Increasing access to specialist care with group medical visits: summary of a pilot in a post-crisis psychiatric clinic - Palay, Josh; Bolton, James M.; Sareen, Jitender; Hensel, Jennifer M. (Frontiers in Health Services, 2023)
Background: Group medical visits (GMVs) have strong evidence of acceptability and effectiveness in the management of chronic medical diseases. Adaptation of GMVs for psychiatric care has potential to increase access, decrease stigma and save costs. Despite promise, this model has not been widely adopted. Methods: A novel GMV pilot was implemented for psychiatric care post-crisis among patients with primary mood or anxiety disorders who required medication management. Participants filled out PHQ-9 and GAD-7 scales at each visit in order to track their progress. After discharge, charts were reviewed for demographics, medication changes and symptom changes. Patient characteristics were compared between those who attended and those who didn’t. Changes in PHQ-9 and GAD-7 scores among attendees were assessed with paired t-tests. Results: Forty-eight patients were enrolled between October 2017 and end of December 2018, 41 of whom consented to participate. Of those, 10 did not attend, 8 attended but did not complete, and 23 completed. Baseline PHQ-9 and GAD-7 scores did not differ significantly between groups. Significant and meaningful reductions in PHQ-9 and GAD-7 scores from baseline to last visit attended occurred among those who attended at least 1 visit (decrease of 5.13 and 5.26 points, respectively). Conclusions: This GMV pilot demonstrated feasibility of the model as well as positive outcomes for patients recruited in a post-crisis setting. This model has the potential to increase access to psychiatric care in the face of limited resources, however the failure of the pilot to sustain highlights challenges to be addressed in future pivots.